The Korean Medicine HOme Medical care for the Elderly (K-HOME) registry: A study protocol for a multicenter registry on aging in place and functional recovery - Hanbit Jin; Yerin Bae; Soomin Song; Hyungsun Jun; Eunji Ahn; Jieun Yu; Beumseuk Kim; Dongsu Kim (PLoS ONE, 2026)
Objective This study aims to evaluate 1-year changes in functional status and aging-in-place (AIP)–relevant outcomes among homebound older adults receiving care through Korean Medicine home medical centers (KM-HMCs). The primary objective is to evaluate changes in activities of daily living measured by the Korean Activities of Daily Living (K-ADL) scale. Secondary objectives are to track major events (mortality, long-term hospitalization, and admission to long-term care facilities) and to examine factors associated with response. Materials and methods This multicenter, prospective, registry-based observational study will be conducted at six KM-HMCs in South Korea. We aim to enroll approximately 250 participants aged 65 years or older with functional decline to obtain an analytic sample of about 200 after expected attrition. Participants will receive usual interprofessional home-based services. The primary outcome is the change in K-ADL from baseline to 1 year. Secondary outcomes include frailty assessed by the Korean version of the FRAIL scale, pain intensity assessed by a numerical rating scale, and AIP-related events. Analyses will use paired tests for changes over 1 year and multivariable logistic regression for factors associated with response, which was operationally defined as a decrease of ≥1 point in the K-ADL score from baseline to 1 year. Discussion This registry will provide standardized longitudinal data on functional status and key events in a routine-care setting, addressing evidence gaps in Korean Medicine home medical care for AIP. Findings may inform evaluation and refinement of the KM-HMC model and guide future research and policy discussions.